2007
DOI: 10.1525/aa.2007.109.2.330
|View full text |Cite
|
Sign up to set email alerts
|

The East Indian Diaspora in Costa Rica: Inbreeding Avoidance, Marriage Patterns, and Cultural Survival

Abstract: Anthropologists have long been interested in the survival of Indian cultural traits in the New World. In this article, we present results of an ongoing project with a Costa Rican community that descends from East Indian indentured servants. We focus on the group's marriage patterns and how these patterns might have helped keep the community as a cohesive ethnic group. We investigate the group's level of inbreeding by computing the inbreeding coefficient using two different methods. We show that the community h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Because there is more variation within than among human groups, when we say that a marker has only been found in a particular region of India, we do not mean that the marker is inexistent someplace else. Madrigal et al (2007) noted that the Culís avoided close kin marriage, a pattern found in Northern/Central non-tribal Indian Hindu communities. They proposed that this cultural trait suggested that the ancestors of the Culís migrated from these regions in prepartition India.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because there is more variation within than among human groups, when we say that a marker has only been found in a particular region of India, we do not mean that the marker is inexistent someplace else. Madrigal et al (2007) noted that the Culís avoided close kin marriage, a pattern found in Northern/Central non-tribal Indian Hindu communities. They proposed that this cultural trait suggested that the ancestors of the Culís migrated from these regions in prepartition India.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we report results of an on-going biocultural investigation with a recently described Indo-Costa Rican population (Madrigal et al, 2007). The group was keenly interested in participating in the genetic aspect of the project, as it wished to know where in prepartition India (or even if) their ancestors came from.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their labor was instrumental for powering the economic sugar boom the Caribbean experienced during the 19th and early 20th centuries. 79,100,115 Extensive anthropological research has been conducted among self-identified Culí communities of East Indian descent living in the coastal region of Puerto Lim on in Costa Rica. 115,116 Combining longterm ethnographic research, including the collection of detailed pedigrees, with the use of uniparental markers, Castrì and coauthors 116 found this community descends from a small number of indentured migrants transported from Central India.…”
Section: East and South Asian Ancestorsmentioning
confidence: 99%